Vibroacoustic Optimization Study for the Volute Casing of a Centrifugal Fan - Jianhua Zhang; Wuli Chu; Jinghui Zhang; Yi Lv (Applied Sciences, 2019)
A numerical optimization is presented to reduce the vibrational noise of a centrifugal fan volute. Minimal vibrational radiated sound power was considered as the aim of the optimization. Three separate parts of volute panel thickness (ST: the side panel thickness; BT: the back panel thickness; FT: the front panel thickness) were taken as the design variables. Then, a vibrational noise optimization control method for the volute casing was proposed that considered the influence of vibroacoustic coupling. The optimization method was mainly divided into three main parts. The first was based on the simulation of unsteady flow to the fan to obtain the vibrational noise source. The second used the design of experiments (DoE) method and a weighted-average surrogate model (radial basis function, or RBF) with three design variables related to the geometries of the three-part volute panel thickness, which was used to provide the basic mathematical model for the optimization of the next part. The third part, implementing the low vibrational noise optimization for the fan volute, applied single-objective (taking volute radiated acoustical power as the objective function) and multi-objective (taking the volute radiated acoustical power and volute total mass as the objective function) methods. In addition, the fan aerodynamic performance, volute casing surface fluctuations, and vibration response were validated by experiments, showing good agreement. The optimization results showed that the vibrational noise optimization method proposed in this study can effectively reduce the vibration noise of the fan, obtaining a maximum value of noise reduction of 7.3 dB. The optimization in this study provides an important technical reference for the design of low vibroacoustic volute centrifugal compressors and fans whose fluids should be strictly kept in the system without any leakage.